On the interplay of network structure and routing strategies for performance in scale-free networks - Ghamry, Walid. K.; Elsayed, Khaled. M. F.; Nassar, Ameen M. (2009 6th International Symposium on High Capacity Optical Networks and Enabling Technologies (HONET), 2009)
Network performance; characterized by the maximum end-to-end traffic flow the network is able to handle without overloading and has as short a route as possible between any two nodes while keeping the congestion in the network as low as possible; is an important issue in the design of Internet Service Provider's topologies. In this paper, we examine how the structural characteristics of network topologies affect the network performance and examine the interplay between structural characteristics of network topologies and routing strategies. We consider routing strategies subject to practical constraints (router technology) and economic considerations (link costs) at layer 3. We propose two new routing methods suitable for implementation in large networks and examine various routing strategies (local, global, and hybrid) with tunable parameters and explore how they can enhance the network performance. We find that there exists an optimal range of values for the tunable parameters to achieve high network performance which depends on the structural properties of the network topology. We also show that our proposal routing scheme with the minimum local information achieves high network performance.